PEMELIHARAAN DAN PERHITUNGAN UMUR TRAFO JARINGAN DISTRIBUSI 20 KV - Syafriyudin; Suyanto, Muhammad; Eko Pambudi, Prastyono (LPPM IST AKPRIND Yogyakarta, 2024)
The distribution transformer is one of the main components in an electric power distribution system. Without a distribution transformer, consumers cannot use electrical energy directly considering that the operating voltage in the distribution system is 20 KV or what is called a medium voltage network. Disruptions that occur in distribution transformers will result in blackouts and obstruction of the distribution of electricity to consumers so that services for electricity needs will be disrupted. For this reason, routine and scheduled maintenance of distribution transformers is required which aims to prevent sudden equipment damage, as well as maintaining optimum equipment work according to its technical age, and safe for humans and the environment, as well as reliable in the electric power distribution system. One of the causes of disruption and damage to transformers include overvoltage due to lightning, overload and unbalanced loads, loss of contact at bushing terminals, broken insulators and failure of transformer oil insulation. These disturbances cause damage to distribution transformers and stop the flow of electricity. to consumers. In calculating the usage time of a transformer, we can predict the usage time of the transformer from calculating the voltage and current used every day, so if we know the usage time of a transformer, we can prevent damage to the distribution network by replacing the transformer before the transformer is damaged.